Aldehyde Reduction by a Pyridone Borane Complex through Boron‐Ligand‐Cooperation: Concerted or Not?. Issue 2 (23rd August 2018) - Müller, Tizian; Hasenbeck, Max; Becker, Jonathan; Gellrich, Urs
Abstract : The reduction of benzaldehyde by a pyridone borane complex was investigated by NMR, X‐ray analysis as well as DFT and DLPNO‐CCSD(T) computations. The reaction leads to the formation of a pyridone boronic ester complex stabilized by an NH··· O hydrogen bond. The computations show that the hydrogenation takes place in a concerted fashion, yielding a transient benzyl alcohol boroxypyridine complex that undergoes a barrierless O–H addition. The concerted hydrogen transfer is associated with a transformation of a pyridone borane to a boroxypyridine, and thus with the interconversion of a neutral donor ligand to a covalently bound substituent. Abstract : Aldehyde reduction by a pyridone borane complex was studied experimentally and computationally. The results indicate that a concerted hydrogen transfer mechanism is operative, resulting in the formation of a transient alcohol complex that undergoes a barrierless addition. The concerted hydrogen transfer is associated with a pyridone borane to boroxypyridine transformation.